Extraction, analysis, anti-tyrosinase activity and formulation of asiaticoside rich fraction from Centella asiatica - Sabar, Aina Mardhiah; Bakhtiar, M. Taher; Amri, Mohamad Shahreen; Darnis, Deny Susanti (2019)
Introduction: The bioactive component of Centella asiatica (L) Urban, asiaticoside is known to exhibit many therapeutic effects. Objectives: This study aimed to develop asiaticoside fractionation method using activated charcoal, evaluate the bioactivity on melanogenesis of the fraction, as well as the optimization and characterization of asiaticoside rich fraction from C. asiatica (CAEMD) hydrogel. Methods: TLC, HPLC, and LC-DAD-ESI-ITMS in positive ion mode were adopted to evaluate asiaticoside in CAEMD fraction qualitatively and quantitatively. Results: The concentration of asiaticoside found was 11.27 % of the CAEMD fraction. In LC-DAD-ESI-ITMS, asiaticoside was found the second most abundant compound in CAEMD and the main fragment ions formed were at m/z 976.25 and m/z 453.33derived from [M+NH4]+ and [M+H-Glu-Glu-Rha-2H2O] respectively. The anti-tyrosinase activity of CAEMD fraction had increased by two-fold compared to the crude extract (p < 0.05) while asiaticoside alone did not show any activity. Carbopol 940 gel containing CAEMD was successfully optimized using three-factor, three-level Box-Behnken design, and C940 0.6 %, TEA 0.27 %, and mixing speed at 650 rpm were selected as the optimized condition. Conclusion: CAEMD fraction has a promising effect on inhibiting melanogenesis pathway and the CAEMD formulation has successfully developed in this study.